Exploring the “family-community” co-parenting model to alleviate parental burnout: a case study of Xi’an, China - Li, Siyu; Zhai, Baoxin; Liu, Junjia (Frontiers in Psychology, 2025)
IntroductionThis study aims to investigate the influence mechanisms of community environments (CE) on parental burnout (PB) among parents of preschool-aged children (0–6 years) in Xi’an, China, while controlling for family environments (FE). A hypothetical framework is proposed to examine the relationships among FE, CE, outdoor parenting activities (outdoor PA), positive parenting emotions (positive PE), and PB.MethodsData were collected through an online survey using a professional questionnaire survey platform (Questionnaire Star) from November 2024 to February 2025, resulting in 308 valid responses. Structural equation modeling (SEM) was employed to test the hypothesized relationships within the proposed framework.ResultsThe results indicate that CE indirectly alleviates PB by promoting outdoor PA. In contrast, FE plays a more central role in directly reducing PB. The study highlights the effectiveness of a “Family-Community” co-parenting model in mitigating PB.DiscussionThis study provides novel insights by integrating PB and positive PE within the same framework, revealing their multidimensional interactions. The findings offer empirical evidence for developing family policies and community services aimed at alleviating PB in urban settings, emphasizing the importance of considering both family and community factors in interventions.